Exploring Parental Attitude and Practices towards Story Book Reading - Marion Sturges, Shelina Bhamani, Asma Hasnain (JECCE, 2023)
This study sought to examine current trends towards shared stories in urban Pakistan. It explored the experiences of the parent’s attitude towards reading and children’s interest in reading. It also looked at the association between parents’ qualifications on child reading and shared reading experiences at home. A cross-sectional survey study design was employed for this study with universal sampling employed to seek data from the parents during August and September 2021. This study found that children benefits greatly when parents share stories with their children. It also found that generally parents who buy and read books themselves supported children to become readers. The findings of this study provide insights into building awareness programs for the parents to provide them with hand on skills to initiate, sustain and promote story reading at home.